Factorial Study of Trunk Size and Shape and Upper Extremities Of Advance Sitting Volleyball Players - Suleiman, Mateen (Journal of Physical Education, 2017)
Sitting volleyball is one of the widely spread sports in the Arabic countries as well as in the whole world including Iraq. This interest in disabled sports lead to interest in studying this sport specially the since and shape of upper extremities and trunk of player because the player perform all skills sitting. The importance of the researcher lies in anthropometric measurements of trunk and upper extremities and players' selection for achieving best results. The aim of the research is to provide a base for selecting adavance sitting volleyball players according to anthropometric measurement. The study was applied on (100) sitting volleyball player using (17) factors that gives detailed information about the shape and size of the players' trunk and upper extremities. The data was collected and treated using SPSS and only (7) factors were selected for their great values. The researcher concluded that there are six factors that were accepted and they are Trunk height from the shoulder in sitting position, humerus and upper extremities length, forearm length, girths, and age and weight.)